Improving maternal and neonatal outcomes through enhanced recovery after caesarean approach: a systematic review - Adebisi, Mathew O.; Adekanye, Emmanuel A.; Afolabi, Oluwasesan B.; Okurumeh, Ogheneovo I.; Amerijoye, Adewale M.; Lawal, Fatai; Akinyoade, Richard A.; Odiegwu, Tobias I.; Adeniyi, Adebayo A. (International Journal of Research in Medical Sciences, 2025)
The responsibilities of caring for the newborn are affected by factors before, during and immediately after caesarean section. Enhanced recovery after caesarean section (ERAC) enables faster return to preoperative functions and thus, has beneficial effects on the mother and her infant. Authors conducted a systematic review of the literature in January 2025 that involved searching 4 databases for peer-reviewed articles on ERAC protocol and traditional techniques between 2015 and 2024. The year of publication, first author’s country, study design, sample size, gestational age, indications for surgery, type of caesarean section and other key findings were extracted from the articles that met the inclusion criteria. The full articles, abstracts, guidelines and conference papers retrieved were 467 with 450 removed for duplications, only abstracts, being guidelines, not meeting our targets and publications outside the stated years. Only 17 articles were included in the review. The primary authors of the included articles originated from 8 countries spanning four (4) continents and 41.2% came from Asia, 23.5% from Africa, and 17.6% each from North America and Europe. Majority (35.3%) of the articles were randomized controlled trials and 29.4% were cohort studies. Interestingly, 88.2% of the articles were published in the last 5 years. Only one study (5.9%) discussed the parental sense of security following discharge from hospital. The socio-demographic variables, past obstetrics, types of caesarean section, gestational age at delivery and type of anaesthesia were factors affecting the success of enhanced recovery after caesarean section and its outcomes.